How Social Media Survey Data is Important for the Long Term Organization’s Decisions - Sukardi, Sukardi; Zauhar, Soesilo; M. , Mas'ud Said; Mardiyono; Wahyudi, Catur (International Journal of Psychosocial Rehabilitation, 2020)
Social media associate degree analytics is also an in vogue chemical analysis technique and is extraordinarily necessary inside the design science technique. It is necessary to analyses large amount data generated by the social media to derive the meaning data from it. However, social media does not contribute to any or all or any phases of favor science technique. It contributes only to three terribly completely different phases of favor science that are define objective, offer answer and completely different one is analysis, and last one is vogue and development. As a result of it is extraordinarily necessary technique, loads of attention have to be compelled to be paid on this system inside the system analysis. This paper will offer the heap of information regarding the social media analytics and its importance inside the terribly completely different fields and improve the use of social media analytics technique and to boot offers the recommendation for the longer-term researchers.